Impacts of heat exposure in utero on longterm health and social outcomes: a systematic review - Norris, Shane; Brink, Nicholas; Lakhoo, Darshnika P.; Solarin, Ijeoma; Maimela, Gloria; von Dadelszen, Peter; Chersich, Matthew F. (BioMed Central (BMC), 2024)
Background: Climate change, particularly global warming, is amongst the greatest threats to human health. While short-term effects of heat exposure in pregnancy, such as preterm birth, are well documented, long-term effects have received less attention. This review aims to systematically assess evidence on the long-term impacts on the foetus of heat exposure in utero. Methods: A search was conducted in August 2019 and updated in April 2023 in MEDLINE(PubMed). We included studies on the relationship of environmental heat exposure during pregnancy and any long-term outcomes. Risk of bias was assessed using tools developed by the Joanna-Briggs Institute, and the evidence was appraised using the GRADE approach. Synthesis without Meta-Analysis (SWiM) guidelines were used. Results: Eighteen thousand six hundred twenty one records were screened, with 29 studies included across six outcome groups. Studies were mostly conducted in high-income countries (n=16/25), in cooler climates. All studies were observational, with 17 cohort, 5 case-control and 8 cross-sectional studies. The timeline of the data is from 1913 to 2019, and individuals ranged in age from neonates to adults, and the elderly. Increasing heat exposure during pregnancy was associated with decreased earnings and lower educational attainment (n=4/6), as well as worsened cardiovascular (n=3/6), respiratory (n=3/3), psychiatric (n=7/12) and anthropometric (n=2/2) outcomes, possibly culminating in increased overall mortality (n=2/3). The effect on female infants was greater than on males in 8 of 9 studies differentiating by sex. The quality of evidence was low in respiratory and longevity outcome groups to very low in all others. Conclusions Increasing heat exposure was associated with a multitude of detrimental outcomes across diverse body systems. The biological pathways involved are yet to be elucidated, but could include epigenetic and developmental perturbations, through interactions with the placenta and inflammation. This highlights the need for further research into the long-term effects of heat exposure, biological pathways, and possible adaptation strategies in studies, particularly in neglected regions. Heat exposure in-utero has the potential to compound existing health and social inequalities. Poor study design of the included studies constrains the conclusions of this review, with heterogenous exposure measures and outcomes rendering comparisons across contexts/studies difficult.
Keywords: Climate change; Heat exposure; Pregnancy; Long-term effects; Socioeconomic impact; Maternal health; Child health; Epigenetics; Metabolic disease; SDG-13: Climate action